2003
DOI: 10.1152/ajpregu.00510.2002
|View full text |Cite
|
Sign up to set email alerts
|

Maturation depresses mouse cerebrovascular tone through endothelium-dependent mechanisms

Abstract: Pearce. Maturation depresses mouse cerebrovascular tone through endothelium-dependent mechanisms. Am J Physiol Regul Integr Comp Physiol 284: R734-R741, 2003. First published December 5, 2002 10.1152/ajpregu.00510.2002In light of previous observations that the range of arterial pressures over which cerebral blood flow is autoregulated differs dramatically in neonates and adults, the present experiments explored the hypothesis that pressure-induced intrinsic arterial tone is regulated differently in neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…Data from the present study suggest that when compared with adult rat cerebral arteries, newborn porcine cerebral arteries exhibit a different pattern of responses to intravascular pressure. One principal difference is that newborn porcine cerebral arteries exhibit significant myogenic tone (ϳ19% of passive diameter) at 10 mmHg, consistent with previous findings in neonatal mouse middle cerebral arteries and newborn porcine mesenteric arteries (16,46). Enhanced sensitivity to stretch has also been reported in the newborn when compared with adult guinea pig large pulmonary arteries (6).…”
Section: Pressure-induced Constriction Occurs Via Voltage-dependent Csupporting
confidence: 88%
See 1 more Smart Citation
“…Data from the present study suggest that when compared with adult rat cerebral arteries, newborn porcine cerebral arteries exhibit a different pattern of responses to intravascular pressure. One principal difference is that newborn porcine cerebral arteries exhibit significant myogenic tone (ϳ19% of passive diameter) at 10 mmHg, consistent with previous findings in neonatal mouse middle cerebral arteries and newborn porcine mesenteric arteries (16,46). Enhanced sensitivity to stretch has also been reported in the newborn when compared with adult guinea pig large pulmonary arteries (6).…”
Section: Pressure-induced Constriction Occurs Via Voltage-dependent Csupporting
confidence: 88%
“…A functional myogenic response is known to be present at the newborn stage of development and appears to involve the activation of voltagedependent Ca 2ϩ channels (17). Similarly, in newborn rodent cerebral arteries, a step increase in intravascular pressure elevates [Ca 2ϩ ] i and induces constriction (16,17,34). Nisoldipine, an L-type Ca 2ϩ channel blocker, reduces arterial wall [Ca 2ϩ ] i and dilates pressurized newborn rat cerebral arteries (17), suggesting that the pressure-induced [Ca 2ϩ ] i elevation occurs due to voltage-dependent Ca 2ϩ channel activation.…”
mentioning
confidence: 99%
“…In the present study, mouse MCAs did not develop myogenic tone in response to pressure and flow. In the absence of luminal flow, previous studies have found that mouse MCAs developed myogenic tone in response to pressure (2,12,13). For example, at 80 mmHg, Ͻ10% tone was observed in MCAs Fig.…”
Section: Mouse Vesselsmentioning
confidence: 93%
“…18,22,23 The cerebral arterial tone is regulated differently in neonates and adults. Cerebral arterial dilatation in newborn piglets is entirely prostanoid dependent, whereas it requires both NO and prostanoids in juveniles.…”
Section: Discussionmentioning
confidence: 99%